Adding MUFA to a dietary portfolio of cholesterol-lowering foods reduces apoAI fractional catabolic rate in subjects with dyslipidaemia - Labonté, Marie-Ève; Jenkins, David J. A.; Lewis, Gary F.; Chiavaroli, Laura; Wong, Julia M. W.; Kendall, Cyril W. C.; Hogue, Jean-Charles; Couture, Patrick; Lamarche, Benoît (British journal of nutrition, 2013)
The present randomised parallel study assessed the impact of adding MUFA to a dietary portfolio of cholesterol-lowering foods on the intravascular kinetics of apoAI- and apoB-containing lipoproteins in subjects with dyslipidaemia. A sample of sixteen men and postmenopausal women consumed a run-in stabilisation diet for 4 weeks. Subjects were then randomly assigned to an experimental dietary portfolio either high or low in MUFA for another 4 weeks. MUFA substituted 13·0 % of total energy from carbohydrate (CHO) in the high-MUFA dietary portfolio. Lipoprotein kinetics were assessed after the run-in and portfolio diets using a primed, constant infusion of [ 2 H 3 ]leucine and multicompartmental modelling. The high-MUFA dietary portfolio resulted in higher apoAI pool size (PS) compared with the low-MUFA dietary portfolio (15·9 % between-diet difference, P = 0·03). This difference appeared to be mainly attributable to a reduction in apoAI fractional catabolic rate (FCR) after the high-MUFA diet ( − 5·6 %, P = 0·02 v . pre-diet values), with no significant change in production rate. The high-MUFA dietary portfolio tended to reduce LDL apoB100 PS compared with the low-MUFA dietary portfolio ( − 28·5 % between-diet difference, P = 0·09), predominantly through an increase in LDL apoB100 FCR (23·2 % between-diet difference, P = 0·04). These data suggest that adding MUFA to a dietary portfolio of cholesterol-lowering foods provides the added advantage of raising HDL primarily through a reduction in HDL clearance rate. Replacing CHO with MUFA in a dietary portfolio may also lead to reductions in LDL apoB100 concentrations primarily by increasing LDL clearance rate, thus potentiating further the well-known cholesterol-lowering effect of this diet.